2021
DOI: 10.1021/jacs.1c02395
|View full text |Cite
|
Sign up to set email alerts
|

Uniform 1D Micelles and Patchy & Block Comicelles via Scalable, One-Step Crystallization-Driven Block Copolymer Self-Assembly

Abstract: Fiber-like (1D) core-crystalline micelles of uniform length can be obtained in protocols involving multiple steps from block copolymers (BCPs) in which crystallization of the core-forming polymer drives the self-assembly. Here we report a systematic study that shows that adding small amounts (<5 w/w%) of a homopolymer corresponding to the core-forming block of the BCP enables uniform 1D micelles (mean lengths L n = 0.6 to 9.7 μm) to be obtained in a single step, simply by heating the mixture in a selective sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 59 publications
0
42
0
Order By: Relevance
“…The micelles with particle size less than 30 nm were formed by self-assembly of amphiphilic properties, while the particle size in this study was larger than 50 nm. Considering that SF micelles were prepared using probe ultrasound, it has been reported that ultrasound can break the micelles into smaller micelles fragments and use these fragments as nuclei to promote micelle growth and finally obtain homogeneous micelles [55]. Therefore, SF micelles may be formed by a "micelle aggregation" [56], which aggregated from small simple micelles to form large complex micelles.…”
Section: Discussionmentioning
confidence: 99%
“…The micelles with particle size less than 30 nm were formed by self-assembly of amphiphilic properties, while the particle size in this study was larger than 50 nm. Considering that SF micelles were prepared using probe ultrasound, it has been reported that ultrasound can break the micelles into smaller micelles fragments and use these fragments as nuclei to promote micelle growth and finally obtain homogeneous micelles [55]. Therefore, SF micelles may be formed by a "micelle aggregation" [56], which aggregated from small simple micelles to form large complex micelles.…”
Section: Discussionmentioning
confidence: 99%
“…If T a is increased well above the T c of both diblock copolymers, again the growth kinetics determine the final observable corona arrangement-i.e., for similar growth rates, a patchy segmentation is generated (Figure 8e). This concept can also be transferred to mixtures of PFS homopolymers and PFS-based BCPs [146]. Due to the higher T c of the PFS homopolymer, a certain fraction of PFS homopolymer crystal fragments will survive upon proper choice of T a ; these fragments then act as seeds upon subsequent cooling and annealing.…”
Section: Co-assembly Of Diblock Copolymersmentioning
confidence: 99%
“…If T a is increased well above the T c of both diblock copolymers, again the growth kinetics determine the final observable corona arrangement—i.e., for similar growth rates, a patchy segmentation is generated ( Figure 8 e). This concept can also be transferred to mixtures of PFS homopolymers and PFS-based BCPs [ 146 ]. Due to the higher T c of the PFS homopolymer, a certain fraction of PFS homopolymer crystal fragments will survive upon proper choice of T a ; these fragments then act as seeds upon subsequent cooling and annealing.…”
Section: Self-assembly Concepts For Patchy Micelles With Crystalline Coresmentioning
confidence: 99%
“…Furthermore, NP hybrid materials with block co-micelles derived from co-assembly of diblock copolymers were reported. Here, the spatially confined incorporation of platinum NPs and CdSe quantum dots was enabled by selective interactions with functional corona patches [ 146 , 178 ].…”
Section: Properties and Applicationsmentioning
confidence: 99%